Moby Dick - Melville, Herman; Brook, Henry; Harvey, Bob (London, Usborne Publishing Ltd, 2006)
A faithful retelling of the classic Herman Melville story about Captain Ahab and his vengeful hunt for the whale Moby Dick. Clearly written in a modern, approachable style, the Classics Retold series is designed to introduce young readers to much-loved classic stories. The text includes informative notes on both the author and the original text, and is ideal for encouraging young readers to pursue an interest in literature